Spiral arms in the protoplanetary disc HD100453 detected with ALMA: evidence for binary–disc interaction and a vertical temperature gradient. Issue 1 (4th November 2019) - Rosotti, G P; Benisty, M; Juhász, A; Teague, R; Clarke, C; Dominik, C; Dullemond, C P; Klaassen, P D; Matrà, L; Stolker, T
ABSTRACT: Scattered light high-resolution imaging of the protoplanetary disc orbiting HD100453 shows two symmetric spiral arms, possibly launched by an external stellar companion. In this paper, we present new, sensitive high-resolution (∼30 mas) Band 7 ALMA observations of this source. This is the first source where we find counterparts in the sub-mm continuum to both scattered light spirals. The CO J  = 3–2 emission line also shows two spiral arms; in this case, they can be traced over a more extended radial range, indicating that the southern spiral arm connects to the companion position. This is clear evidence that the companion is responsible for launching the spirals. The pitch angle of the submillimetre continuum spirals (∼6°) is lower than the one in scattered light (∼16°). We show that hydrodynamical simulations of binary–disc interaction can account for the difference in pitch angle only if one takes into account that the mid-plane is colder than the upper layers of the disc, as expected for the case of externally irradiated discs.